ANALISIS PENGELOLAAN RANTAI PASOK TEPUNG KELAPA PADA PT. XYZ DI SULAWESI UTARA - Chintya Stefanny Anis; Agnes E. Loho; Grace A. J. Rumagit (Sam Ratulangi University, 2017)
The purpose of this study are: (1) Identify the supply chain model of coconut desiccated at PT. XYZ and (2) to analyze the supply chain management of desiccated coconut at PT. XYZ. The research was conducted over 2 months ie from September to November 2016 and is located in PT. XYZ (pseudonym), in North Sulawesi. The data used in this research are primary and secondary data. The primary data obtained through field observation and direct interviews. Interviews were conducted with the company related logistics company to find a picture of the supply chain and supply chain management is done by the company. In addition, the researchers also conducted interviews with coconut farmers and collectors to determine the condition of the current coconut price as well as the flow of raw material coconuts from the famers to supplier. Secondary data were obtained from the relevant literature, as well as documents and reports that are owned by companies and agencies. This study focuses on the management of the flow of material and information flow of the supply chain of coconut flour at PT. XYZ. The results of observations and interviews were analyzed with descriptive qualitative analysis methods. The results showed that (1) Members of coconut flour supply chain at. XYZ, namely (a) the raw material supplier of coconut spread in some areas, (b) PT. XYZ for purchasing, sales, shipping and production, (c) Expediting Services to send products from Bitung harbor, next to the port of Tanjung Priok to be exported to the country of destination, (d) The customer, in this case the food companies that require raw materials coconut flour to be produced into chocolate bars, cookies, dessert, and so forth. (2) (a) Selection of supplier PT. XYZ is good enough, because every supplier who will supply the raw material to go through the interview stage, made a deal with the company and agree to the terms proposed by the company. PT. XYZ also maintain good relations with its suppliers with visits annually; (b) the flow of material and information flow is managed by PT. XYZ is good enough. Any information purchasing, sales, shipping and finance centered PT.XYZ headquarters is located in Manado and PT. XYZ manage information about the quantity of raw materials available in the warehouse and general condition of the plant.